Propostas de atividades com estratégias metodológicas diversificadas para a alfabetização científica sobre enteroparasitoses humanas - Amélia Esteves Ribeiro (2020)
In the face of the extensive content and ineffective teaching strategies, it is up to the teacher to focus on relevant topics and choose new strategies that allow scientific literacy. In this regard, health related subjects should be prioritized as a way of improving students' life conditions by preparing them to face potential health risks. For this reason, intestinal parasitic diseases, considered by the World Health Organization as neglected diseases, require emphasis. Furthermore, the use of active methodological strategies is proven to be efficient to provide the possibility of building solid knowledge. This work aimed at the development of enteroparasitic activities, which will be made available to high school Biology. Thus, activities with an investigative bias were developed for the elaboration of an educational product, in order to promote students' scientific literacy. The analysis and evaluation of the product were carried out by 44 Biology teachers, enrolled in the Professional Master's Degree in Biology Teaching (PROFBIO) in 2018. Data collection was performed using an online questionnaire. After evaluations, the educational product was considered appropriate to be applied in high school by 93.2% of the interviewees, as they considered the topic relevant and the activities suitable for this age group. In addition, to 97.7% of the teachers the activities will be able to guarantee the students’ protagonism. 68% of the interviewees indicated the activities have some innovation and 59% indicated that they have an investigative bias. Further, 95.5% of the teachers considered the activities feasible for they required easily accessible materials. According to 86.4% of evaluators, with the execution of the proposed activities, students will be able to fully understand the meaning of the concepts learned, applying them in everyday situations.